Remotely triggered micro‐earthquakes in the Larderello‐Travale Geothermal Field (Italy) following the 2012 May 20, Mw 5.9 Po‐plain earthquake. Issue 5 (14th March 2013) - Saccorotti, G.; Piccinini, D.; Mazzarini, F.; Zupo, M.
Abstract [1] We report observations of remotely triggered earthquakes at the Larderello‐Travale Geothermal Field (Italy), following the Mw = 5.9 Po‐Plain earthquake on 20 May 2012. Four distinct triggered events are recognized within a short ( 25 s) time interval accompanying the sweeping of 10s Rayleigh waves. Triggered sources are clustered at depths in between 4 km and 6 km. The magnitude and distance of the mainshock agree well with the triggering threshold previously proposed for The Geysers, California. For three out of four earthquakes, the Rayleigh wave dynamic stresses are mostly associated with extensional vertical (szz) and shear (sxz) components, which range up to 5 KPa. Once considering the structural setting of the area, the most likely triggering mechanism involves the rupture of normal faults which are kept close to failure by high‐pressure crustal fluids.